Comparison of Experienced Violence in Women with Opiate-Dependent and Stimulant-Dependent Husbands - Neda Ahmadpour; Ali Farhoudian; Ali Asgari; Manouchehr Azkhosh; Omid Massah (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: Opium and stimulants are two kinds of illegal substances which are different from each other in chemical structure, psychological and biological effects (material), and their potential adverse effects on consumers. The present study compares the effect of abuse of each of the two (opium and stimulants) on violent behavior against wives. Materials & Methods: The present study was a non-experimental and comparative study. The study sample included 100 spouses of men addicted to opium and stimulants (50 opium and 50 stimulant addicts) who attended governmental or non-governmental centers or camps in Tehran city (from October 2011 to January 2012), in order to receive professional assistances. (Both groups of subjects were selected by convenient sampling method to ensure the compatibility with input and output data. The "revised conflict tactics scale" was used to assess the rates of violence (psychological, sexual coercion, negotiation, injury and physical assault) exerted by men. Results were analyzed using multi-variety analysis of variance and covariance. Results: Results showed that after controlling the age as a covariate, consumers of stimulants (especially methamphetamine) were more violent toward their wives than were consumers of opium (P&le0.001). There were also significant differences between the two groups in the psychological, sexual coercion, injury and physical assault subscales, but not in the negotiation subscale (P&le0.05). Conclusion: It seems that the psychopharmacological effect of stimulants leads to more violent behaviors in its consumers (especially by methamphetamine) than in consumers of opium.